7 - Review Article: Piet Konings and Francis Nyamnjoh, 2003, Negotiating an Anglophone Identity. A Study of the Politics of Recognition and Representation in Cameroon, Brill, Leiden, and Boston: African Studies Series, 230 pp. Maps, biblio - Fru, Nicodemus Awesome (Africa Development, 2004)
abstract